Conference of Arctic Parliamentarians (CPAR) (2009)
The Conference of Parliamentarians of the Arctic Region (CPAR) is a parliamentary body comprising delegations appointed by the national parliaments of the Arctic states (Canada, Denmark, Finland, Iceland, Norway, Russia, Sweden, U.S.A.) and the European Parliament. The conference also includes Permanent Participants representing Indigenous peoples, as well as observers.